Creativity in Rejung Oral Literature Art in Bengkulu (Catharsis, 2022)
Traditional art is a regional art that becomes the identity of its supporting community. The changing times have resulted in abandoning traditional arts, but a process of change or renewal cannot be avoided. Therefore, it requires awareness from artists or supporting communities, creative thinking, and a creative process to make traditional arts continue to develop in the community. Through creativity, it is expected that a person or a group of people can innovate to inherit and preserve traditional art. This study has examined a music community, the BESOK, which has created creativity in the Rejung Bengkulu art. The approach in this study used descriptive qualitative methods with case studies (real-life events). Data and data sources were obtained through primary data and secondary data. Data collection used observation, interviews, and documentation studies. The validity technique employed the criterion of the degree of confidence (credibility) with the triangulation technique. Data analysis was conducted through data collection, reduction, presentation, and verification. The results of the study are as follows. The creativity carried out by the BESOK community is due to the emergence of the personnel's restlessness by seeing the phenomena and facts around them. They feel that the traditional art of Rejung is starting to be forgotten, and only a few people who play and know it. Thus, the nature of their initiative and motivation to carry out the preservation and existence of a Bengkulu traditional art emerges. Through the BESOK community's creativity, four dimensions of creativity were analyzed through the art. They are the personal dimension, the press dimension, the process dimension, and the product dimension.